CORPORATE BOND PRICE PHENOMENON ON THE INDONESIA STOCK EXCHANGE IN 2016-2018 - Yunike Berry (Manajemen Bisnis, 2021)
This research was conducted at the companies which issuing corporate bonds in the Indonesia Stock Exchange in periode of 2016-2018. Total sample used are 64 corporate obligation, with purposive sampling method. This research used quantitave data. The analysis technique data used in this research is multiple linear regressions. Based on the results of the analysis found that interest rates have a significant positive effect on changes in bond prices. Bond coupons have a significant positive effect on bond prices. The age of the bonds does not have a significant effect on changes in bond prices. Bond ratings do not have a significant effect on changes in bond prices.